Assessment of the adhesive capacity of asphalt binders in the aggregatebinder bonds by means of new methodology. - Valdés Vidal, Gonzalo; Miró Recasens, Rodrigo; Martínez Reguero, Adriana (Revista de la Construcción. Journal of Construction, 2015)
The main goal of this study is to present a new methodology to characterize the adhesive capacity (cohesion and adhesion capacity) of asphalt binders by means of new mechanical parameters. This methodology is based on the Fenix test, a test recently developed in Spain. This method assesses the cracking resistance of the asphalt mixtures, and it has been adapted to characterize the bonding power of asphalt binders. The main parameters achieved with this procedure are related to the energy dissipated during the breaking between the asphalt binder and the aggregate, when these materials are subjected to tensile stress; essential parameters related to the adhesive capacity of asphalt binders. The results of an experimental stage are presented in this research, in which the proposed methodology has been applied to analyse the behaviour of the binder in the aggregate-binder matrix according to temperature variation and the effect of water and ageing; taking into account aggregates of the same origin and with a different shape pattern. The results show that the parameters achieved from this new methodology allows characterizing the adhesive capacity of asphalt binders in the different conditions assessed.